2017
DOI: 10.3390/ijms18040873
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock, Cell Division, and Cancer: From Molecules to Organism

Abstract: As a response to environmental changes driven by the Earth’s axial rotation, most organisms evolved an internal biological timer—the so called circadian clock—which regulates physiology and behavior in a rhythmic fashion. Emerging evidence suggests an intimate interplay between the circadian clock and another fundamental rhythmic process, the cell cycle. However, the precise mechanisms of this connection are not fully understood. Disruption of circadian rhythms has a profound impact on cell division and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 131 publications
2
112
0
4
Order By: Relevance
“…The circadian clock controls diverse cellular processes, including the cell cycle, DNA damage response and apoptosis, by regulating genes, such as p16 , p21 , Cyclin D1 , Wee1 and p53. 38,91–93 These molecular links further support the notion that disruption of circadian regulation promotes cancer phenotypes, such as rapid proliferation, impairment of DNA repair and resistance to apoptosis. Given the potential significance of dedifferentiation processes in carcinogenesis, it is critical to understand the effects of global epigenetic changes on the circadian clock and how the circadian clock is regulated in developing cancer cells (Fig.…”
Section: Impact Of Circadian Clock Disruption On Cancer Developmentsupporting
confidence: 52%
“…The circadian clock controls diverse cellular processes, including the cell cycle, DNA damage response and apoptosis, by regulating genes, such as p16 , p21 , Cyclin D1 , Wee1 and p53. 38,91–93 These molecular links further support the notion that disruption of circadian regulation promotes cancer phenotypes, such as rapid proliferation, impairment of DNA repair and resistance to apoptosis. Given the potential significance of dedifferentiation processes in carcinogenesis, it is critical to understand the effects of global epigenetic changes on the circadian clock and how the circadian clock is regulated in developing cancer cells (Fig.…”
Section: Impact Of Circadian Clock Disruption On Cancer Developmentsupporting
confidence: 52%
“…As chronic circadian disruption via shift work, increased exposure to light at night, and inadequate daylight exposure become increasingly pervasive in modern society, so have we seen an increase in diseases linked to chronic circadian disruption, such as cancer, obesity, diabetes and cardiovascular and neurodegenerative disease (Evans and Davidson, 2013;Musiek and Holtzman, 2016;Shostak, 2017). Inflammation plays an important part in the pathology of all these diseases, leading many to hypothesize that the dysregulation of immunity plays a major role in the link between chronic circadian disruption and associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been proposed that disruption of circadian rhythm may contribute to the development of cancer, and shift work involving circadian disruption has been classified as a probable carcinogen to human beings by the International Agency for Research on Cancer . Epidemiological studies have shown that circadian disruption is significantly associated with increased risk of a range of malignancies, such as breast and prostate cancer .…”
Section: Discussionmentioning
confidence: 99%